Penerapan Fungsi-Fungsi Administrasi Di Sd Terpadu Muhammadiyah 36 Medan - Mursal Aziz; Sabina Khairunnisa; Aviva Hanum Siregar; Nur Hafni Bahri Siambaton (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Administration plays an important role in the success of a school, of course this must be supported by how the application of administrative functions is orderly and organized. This study aims to determine how the application of administrative functions in the Integrated School of Muhamadiyah 36 Medan. This research was conducted with a qualitative method in the form of a survey. The source of data to be obtained comes from the results of interviews and observations of teachers and administrative staff. The results of the research obtained state that Muhamdiyah 36 Medan Integrated Elementary School is an orderly and organized educational institution in accordance with the role of administrative functions to be achieved.